Tubular triazine TCN / FePc nanodot bifunctional catalyst as well as preparation method and application thereof
FePc nanodots were prepared by calcining the surface of the tubular triazine TCN catalyst to construct a bifunctional catalytic system, which solved the problem of low photocatalytic rate and degradation rate of existing carbon nitride photocatalysts and achieved efficient photocatalytic degradation of antibiotics.
Patent Information
- Application Number
- CN202411644067.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
AI Technical Summary
The existing carbon nitride (g-C3N4) photocatalysts have problems such as low specific surface area, easy photocarrier recombination and strict pH range requirements, resulting in low photocatalysis rate and low degradation rate.
FePc nanodot-modified tubular triazine TCN catalyst was prepared by calcination method to construct a bifunctional catalytic system and improve the efficiency of photogenerated carrier generation and separation.
The efficiency of photocatalytic degradation of antibiotics is significantly improved, the utilization rate of visible light by the catalyst is improved, and the stability of the catalyst is enhanced.
Smart Images

Figure HDA0005139246590000011 
Figure HDA0005139246590000012 
Figure HDA0005139246590000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and particularly relates to a method for preparing an iron phthalocyanine (FePc) nanodot-modified tubular triazine carbon nitride (TCN) photocatalyst. Background Art
[0002] Environmental pollution is becoming increasingly serious, posing a huge challenge to the sustainable development of social economy. Antibiotics such as tetracycline, penicillin and amoxicillin, as organic pollutants, are present in large quantities in wastewater discharge from medicine, animal husbandry and heavy industry, which has attracted widespread attention from the academic community. Therefore, it is urgent to develop new green and sustainable technologies to remove antibiotics from the environment. Photocatalytic technology uses photocatalysts such as semiconductors to accelerate chemical reactions under the action of solar energy, effectively solving pollution problems in water and soil.
[0003] As one of the advanced oxidation technologies, Fenton technology is regarded as a very promising solution for efficiently degrading emerging organic pollutants such as antibiotics by generating a large amount of reactive oxygen species (ROS). Carbon nitride (g-C3N4) is widely regarded as an important candidate for future photocatalytic materials due to its advantages such as simple synthesis, low cost, non-toxicity and moderate band gap. However, bulk g-C3N4 (BCN) also has a series of problems, such as low specific surface area, easy recombination of photogenerated carriers, strict pH range requirements, etc., resulting in low photocatalytic rate and low photocatalytic degradation rate of g-C3N4. Therefore, obtaining a carbon nitride composite photocatalyst with high photocatalytic activity is of great significance for better removal of antibiotics in the environment. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a tubular triazine TCN / FePc nanodot bifunctional catalyst. The catalyst is prepared by a calcination method to prepare a FePc nanodot-modified TCN catalyst, promote the generation of photogenerated carriers, accelerate their separation and transfer, and thus improve the efficiency of photocatalytic degradation of antibiotics.
[0005] The technical solution of the present invention:
[0006] A tubular triazine TCN / FePc nanodot bifunctional catalyst, wherein the catalyst presents a hollow tubular structure, the hollow tube is about 7.4 μm long and about 1.6 μm in diameter, and the triazine tubular carbon nitride has no obvious pore structure, has a uniform thickness, and has a rough material surface.
[0007] A method for preparing a tubular triazine TCN / FePc nanodot bifunctional catalyst comprises the following steps: synthesizing TCN by a simple water bath heating and calcination method, grinding a FePc monomer and mixing it with TCN in a certain proportion, and obtaining a FePc nanodot / TCN composite photocatalyst by a calcination method.
[0008] Beneficial effects of the present invention:
[0009] 1. From the perspective of the preparation method, precursor and product, this invention uses green and environmentally friendly composite materials and will not pollute the environment.
[0010] 2. This application constructs a FePc / TCN composite material, which can effectively improve the utilization rate of the catalyst for visible light, generate more photogenerated carriers, and promote the separation and transfer of electron-hole pairs. FePc is evenly dispersed on the surface of TCN, and there is basically no agglomeration phenomenon, which is conducive to the migration of photogenerated electrons at the interface between the two, thereby improving the efficiency of photocatalysis. The invention uses TCN as a one-dimensional nanotube structure with a large specific surface area and a smaller pore size, providing a large number of active sites for the subsequent FePc / TCN photo-Fenton system. A dual-reaction center catalytic system with a synergistic effect is designed and constructed, in which the photocatalytic reaction center is mainly TCN and the Fenton reaction center is mainly FePc, thereby significantly improving the photodegradation efficiency of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0012] Figure 1 a is the XRD patterns of TCN, BCN and 3% FePc / TCN.
[0013] Figure 1 b is the FT-IR spectrum of TCN, BCN and 3%-FePc / TCN.
[0014] Figure 2 a, 2b are TEM images of 3%-FePc / TCN.
[0015] Figure 2 c, 2d are HRTEM images of 3%-FePc / TCN.
[0016] Figure 3 a is the N2 adsorption-desorption isotherms of TCN and 3%-FePc / TCN.
[0017] Figure 3 b is the pore size distribution diagram of TCN and 3%-FePc / TCN.
[0018] Figure 4 a is the XPS full spectrum of TCN and 3%-FePc / TCN.
[0019] Figure 4 b C1s high-resolution XPS spectra of TCN and 3%-FePc / TCN.
[0020] Figure 4 c N1s high-resolution XPS spectra of TCN and 3%-FePc / TCN.
[0021] Figure 4 d is the Fe 2p high-resolution XPS spectrum of 3%-FePc / TCN.
[0022] Figure 5 a is the UV-visible diffuse reflectance spectra of BCN, TCN and 3%-FePc / TCN composites.
[0023] Figure 5 b is the band gap value of BCN, TCN and 3%-FePc / TCN composite materials.
[0024] Figure 5 c is the valence band XPS spectra of TCN and 3%-FePc / TCN composite materials.
[0025] Figure 5 d is a schematic diagram of the energy band structure of TCN and 3%-FePc / TCN composite nanomaterials.
[0026] Figure 6 a is the photo-Fenton degradation curve of TC under different catalysts.
[0027] Figure 6 b is the degradation curve of TC in 3%-FePc / TCN system under different catalyst dosages.
[0028] Figure 6 c is the degradation curve of TC at different pH in 3%-FePc / TCN system.
[0029] Figure 6 d is the UV-visible absorption spectrum of TC degrading 3%-FePc / TCN under different irradiation times.
[0030] Figure 6 e is the degradation curve of TC under different combinations of visible light and H2O2 in the 3%-FePc / TCN system.
[0031] Figure 6 f is the photo-Fenton degradation stability study of 3%-FePc / TCN semiconductor nanocomposites.
[0032] Figure 7 a is the PL spectra of TCN and 3%-FePc / TCN.
[0033] Figure 7 b is the time-resolved fluorescence decay fitting curve of TCN and 3%-FePc / TCN.
[0034] Figure 7 c is the transient photocurrent response of TCN and 3%-FePc / TCN.
[0035] Figure 7 d is the electrochemical impedance spectra of TCN and 3%-FePc / TCN. DETAILED DESCRIPTION
[0036] In order to solve the problems in the background technology, a preparation method and application of a tubular triazine TCN / FePc nanodot bifunctional catalyst is invented to solve the problems of low photocatalytic rate and low photocatalytic degradation rate of g-C3N4 (BCN).
[0037] In order to improve the photocatalytic efficiency of g-C3N4 (BCN), the present application prepares g-C3N4 (TCN) with a one-dimensional tubular triazine ring structure, thereby improving the defects. At the same time, in order to further improve the degradation rate, FePc nanodots are loaded on its surface to construct a dual-functional catalytic system. The introduction of FePc enhances the catalyst's ability to absorb visible light to a certain extent, promotes the generation of more photogenerated carriers, and thus improves the photocatalytic degradation efficiency. The FePc nanodots are evenly distributed on the surface of TCN, and basically no agglomeration occurs, which is conducive to the effective transmission of photogenerated electrons at the interface between the two, thereby effectively improving the efficiency of the photocatalytic reaction. Therefore, we designed a TCN with a one-dimensional tubular triazine ring structural unit, and then successfully loaded FePc onto TCN by calcination, and designed a dual reaction center catalytic system with a synergistic effect. Among them, the photocatalytic reaction center is mainly TCN, and the Fenton reaction center is mainly FePc, which significantly enhances the degradation rate of tetracycline (TC).
[0038] Tubular triazine TCN / FePc nanodots bifunctional catalyst
[0039] A tubular carbon nitride photocatalytic material having a one-dimensional tubular triazine ring structural unit, which presents a hollow tubular structure, the length of the hollow tube is about 7.4 μm, and the diameter is about 1.6 μm. In addition, the triazine tubular carbon nitride has no obvious pore structure, has a uniform thickness, and has a rough surface.
[0040] TCN was synthesized using a simple water bath heating and calcination method. The FePc monomer was ground and then mixed with TCN in a certain proportion, and the FePc nanodot / TCN composite photocatalyst was obtained using a calcination method.
[0041] Preparation method of tubular triazine TCN / FePc nanodot bifunctional catalyst
[0042] Embodiment 1:
[0043] Step 1: Preparation of TCN
[0044] (1) 600 mg of melamine, 3.3 g of potassium chloride and 2.7 g of lithium chloride were put into an agate grinding body and ground for 1 h, and the ground mixture was placed in a crucible with a lid.
[0045] (2) The ground mixture was placed in a muffle furnace with an air atmosphere and heated at 550°C at a rate of 5°C / min.
[0046] Heat for 4h.
[0047] (3) The obtained precursor was centrifugally washed with boiling water and ethanol, and then placed in an oven at 60°C.
[0048] The mixture was heated at 400 °C for 12 h for drying to obtain carbon nitride with a triazine ring structure, which was named TCN.
[0049] Step 2: Preparation of FePc (ferrophthalocyanine) / TCN (carbon nitride)
[0050] (1) First, FePc monomer was placed in an agate mortar and ground for 1 h.
[0051] (2) 0.01 g of ground FePc and 1 g of TCN monomer were mixed, and the precursor was placed in an uncovered porcelain boat and calcined in a tube furnace (argon) (heating rate 5°C / min, heating temperature 400°C, heating time 120 min).
[0052] (3) After calcination, FePc / TCN composite material can be obtained.
[0053] Embodiment 2:
[0054] In the FePc / TCN preparation step, 0.005 g of FePc and 1 g of TCN monomer were mixed, and the other steps remained unchanged.
[0055] Embodiment 3:
[0056] In the FePc / TCN preparation step, 0.03 g of FePc and 1 g of TCN monomer were mixed, and other steps remained unchanged, thereby generating a 3%-FePc / TCN composite material.
[0057] Embodiment 4:
[0058] In the FePc / TCN preparation step, 0.05 g of FePc and 1 g of TCN monomer were mixed, and the other steps remained unchanged.
[0059] Application of tubular triazine TCN / FePc nanodots bifunctional catalyst
[0060] The catalyst of the present application is used for removing antibiotic pollutants in the environment, especially removing tetracycline (TC), and significantly improves the removal rate to 92.3%. After multiple cycle tests, the degradation rate of TC is still as high as 89%.
[0061] Specific steps for removing tetracycline (TC):
[0062] A photochemical reactor was used to conduct a photocatalytic degradation experiment on TC under the irradiation of a 300W xenon lamp with a wavelength of λ>420nm to determine the degradation of the sample. First, 3mg~50mg of catalyst was added to 50mL of 20mg / L TC solution, and the reaction was carried out in the dark for 30min to reach adsorption-desorption equilibrium. During this period, 4mL of the suspension was taken out every 10min and centrifuged to obtain the supernatant. 10μL H2O2 was added at the beginning of the photoreaction, and 4mL of the suspension was centrifuged every 20min. The supernatant of the photoreaction process was obtained by centrifugation, and finally the concentration of TC in each supernatant was determined by a UV-visible spectrophotometer.
[0063] The formula of photocatalytic degradation rate is: D = (C0-C t ) / C0×100%.
[0064] Where: C0 is the initial concentration of TC, in mg·L -1 . C t is the concentration of TC after time t, in mg·L -1 .
[0065] For every 50 mL of 20 mg / L tetracycline solution, the amount of the catalyst is 3 mg, 5 mg, 10 mg, 20 mg or 50 mg.
[0066] Detailed description with drawings
[0067] Figure 1a is the XRD pattern of the prepared samples TCN, BCN and 3% FePc / TCN. In the XRD spectrum, BCN has characteristic peaks at 13.12° and 27.13°, corresponding to the (100) and (002) crystal planes of bulk carbon nitride, respectively, representing the planar stacking and interlayer stacking of the conjugated aromatic system. TCN has five characteristic peaks at 12.0°, 20.9°, 26.5°, 29.3° and 32.3°, corresponding to the (100), (110), (002), (102) and (210) crystal planes of bulk carbon nitride, respectively. Among them, 12.0° and 26.5° correspond to the planar stacking and interlayer stacking of triazine rings. It is worth noting that the characteristic peaks of FePc were not found in 3%-FePc / TCN, which may be due to the small actual loading amount of FePc and its high dispersion. In addition, the characteristic peaks of 3%-FePc / TCN are basically the same as those of TCN, indicating that 3%-FePc / TCN has been successfully prepared. Figure 1 b) In the spectrum, BCN, TCN and 3%-FePc / TCN show similar basic frameworks. -1 The characteristic peak at 1200-1710cm -1 The characteristic peak at 3077-3600cm corresponds to the stretching vibration of the CN heterocycle. -1 It corresponds to the stretching vibration of OH / NH2. Similarly, due to the high dispersion of amorphous FePc, no characteristic peak of FePc was found in 3%-FePc / TCN semiconductor material, which is consistent with XRD.
[0068] Figure 2 a and b are transmission electron microscope photos of 3%-FePc / TCN. It is not difficult to see that 3%-FePc / TCN is a one-dimensional nanotube structure. Figure 2 c shows that FePc is evenly dispersed on the TCN surface with almost no agglomeration, which is conducive to the migration of photogenerated electrons at the interface between the two, thereby improving the efficiency of photocatalysis. Figure 2 In d, it can be observed that 3%-FePc / TCN has clear lattice fringes with a distance of about 0.73nm, which is assigned to the 002 plane and corresponds to the in-plane periodicity of the triazine structural unit. At the same time, the appearance of lattice fringes also indicates that 3%-FePc / TCN is a crystalline structure.
[0069] Figure 3 a and b are the N2 adsorption-desorption isotherms and pore size distribution curves of TCN and 3%-FePc / TCN, respectively. The results show that both TCN and 3%-FePc / TCN exhibit type IV adsorption isotherms, indicating that both have mesoporous structures. It is worth noting that the specific surface areas of TCN and 3%-FePc / TCN are 90.48 and 90.16 m2 / g, indicating that the specific surface area of TCN remains basically unchanged after loading FePc; the average pore sizes of the two are 7.78 and 6.60nm, indicating that TCN loaded with FePc has a smaller pore size.
[0070] Figure 4 XPS spectra of TCN and 3%-FePc / TCN. TCN and 3%-FePc / TCN have similar full XPS spectra. It is worth noting that in addition to the common C, N, and O elements of the two, 3%-FePc / TCN also has a trace amount of Fe element. This shows that the 3%-FePc / TCN nanocomposite has been successfully prepared. There are four characteristic peaks at 284.8, 285.4, 288.0 and 293.0 eV in the X-ray photoelectron C1s high-resolution spectrum of 3%-FePc / TCN, corresponding to aromatic carbon (C=C), cyano, triazine ring structure NC=N and graphene interlayer π-π* excitation, respectively. The high-resolution spectrum of the 3%-FePc / TCN sample N1s has three characteristic peaks at 398.6, 400.3 and 403.9 eV, which are assigned to sp 2 Hybrid nitrogen (CN=C), quaternary nitrogen (C-NH x ) and delocalized π excitation. It is worth noting that the N1s binding energy of 3%-FePc / TCN is slightly shifted toward the low binding energy direction compared to TCN, which indicates that more electrons will gather around N. The Fe 2p high-resolution spectrum of 3%-FePc / TCN shows that the Fe-N peak intensity in the spectrum is very low, which is caused by the extremely low FePc content in 3%-FePc / TCN. Among them, the two characteristic peaks at 710.4 and 712.7 eV correspond to Fe 3+ 2p 3 / 2 and Fe 2+ 2p 3 / 2 , while the characteristic peaks at 723.2 and 725.3 eV correspond to Fe 2p 1 / 2 X-ray photoelectron spectroscopy showed that TCN and FePc were successfully composited.
[0071] Figure 5 a is the UV-visible diffuse reflectance spectra (UV-DRS) of TCN and 3%-FePc / TCN. It is not difficult to see that compared with BCN, TCN and 3%-FePc / TCN have stronger visible light absorption ability, which is attributed to the introduction of FePc. Therefore, the introduction of FePc improves the utilization rate of the catalyst for visible light to a certain extent, generates more photogenerated carriers, and thus improves the photo-Fenton degradation rate of TC. In addition, the band gaps (E g ) can be calculated according to the formula αhν=A(hν-E g ) 1 / 2It is found that they are 2.69, 2.79 and 2.67 eV respectively. Figure 5 b shows the band gap energy of BCN, TCN and 3%-FePc / TCN samples. The valence band energy (E) of TCN and 3%-FePc / TCN was determined by VB-XPS spectra. VB ), 1.60 and 1.53 eV vs. NHE, respectively. Figure 5 c. Finally, through the formula (E VB =E g +E CB )TCN and 3%-FePc / TCN conduction band energy (E CB ) are -1.19eV and -1.14eV respectively, and the energy band structure diagrams of the two are drawn, as shown in Figure 5 d. It is not difficult to find that the introduction of FePc not only enhances the absorption capacity of semiconductor catalysts to visible light, but also narrows its band gap.
[0072] Figure 6 a is the photo-Fenton performance of all samples for TC (tetracycline). It can be seen from the figure that the photo-Fenton performance of the 3%-FePc / TCN+H2O2+vis system is the best, and 73.2% TC degradation can be achieved within 120 minutes. Under the same conditions, the TC removal rates of BCN, TCN, 1%-FePc / TCN, 5%-FePc / TCN and 10%-FePc / TCN are 59.8%, 61.6%, 71.6%, 72.1% and 62.0%, respectively. The data show that the TC degradation rate can be significantly improved after the appropriate amount of FePc is coupled with TCN. Figure 6 b. The effect of catalyst dosage on TC degradation was studied. Overall, when the catalyst dosage gradually increased from 3 mg to 50 mg, the degradation rate of TC first increased and then decreased, and the effect was optimal when the dosage was 20 mg. This is mainly because too little catalyst cannot generate a large number of photogenerated carriers and provide sufficient active sites, while excessive catalyst may hinder the mass transfer efficiency of photogenerated carriers. HCl and NaOH solutions were used to explore the effect of pH in the system on the degradation rate. The measurement results are shown in Figure 2. Figure 6 c. When the pH value of the system is 3, the catalyst has the strongest degradation performance, which can reach 92.3%. However, when the pH value in the system is gradually increased by using NaOH solution, although the adsorption of the dark reaction is enhanced, the degradation rate of the light reaction is getting less and less. This may be because as the pH increases, the oxidation ability of ·OH decreases, and at the same time, Fe 3+ The active sites will be OH - Occupancy, resulting in Fe 3+ The interaction with H2O2 is inhibited. In addition, Figure 6d is the liquid UV absorption spectrum of TC degradation in the 3%-FePc / TCN+H2O2+vis system. It can be seen that in the adsorption stage of the dark reaction (the first 30 minutes), the absorption wavelength at 357nm basically did not change, but in the light reaction stage (the last 120 minutes), the absorption wavelength began to drop rapidly, indicating that TC was effectively destroyed and removed in the photo-Fenton reaction. Figure 6 e investigated the photocatalytic performance under different conditions. When there was only a semiconductor catalyst and a catalyst and visible light in the system, the degradation rates of TC were 7% and 11.2%, respectively. However, when the system contained catalyst + H2O2 and catalyst + H2O2 + visible light, the degradation rates of TC were 79.1% and 92.3%, respectively. This shows that the system is dominated by Fenton reaction and supplemented by photocatalytic reaction. Finally, the stability of the semiconductor catalyst was determined through 4 cycle experiments, and the results are as follows Figure 6 f. It is worth noting that after multiple cycles of testing, the degradation rate of TC is still high (89%), which indicates that 3%-FePc / TCN has extremely strong stability.
[0073] Steady-state photoluminescence spectroscopy (PL) and time-resolved transient fluorescence were used to investigate the transfer and recombination of surface photogenerated carriers between 3%-FePc / TCN and TCN. Figure 7 a and b. Overall, the PL emission peak of the 3%-FePc / TCN semiconductor catalyst is significantly weaker than that of TCN (the weaker the emission peak, the higher the charge transfer efficiency). At the same time, the average carrier lifetimes of 3%-FePc / TCN and TCN are 4.62 and 4.38ns, respectively. The two data show that the coupling of FePc and TCN can accelerate the separation and migration of photogenerated carriers and reduce the recombination rate. In the transient photocurrent test, the separation rate of electron-hole pairs is generally positively correlated with the photocurrent intensity. The test results are shown in Figure 7 c. The maximum photocurrent response of 3%-FePc / UPCN is 0.8050 μA / cm 2 , and is about TCN (0.4050μA / cm 2 ) times. Figure 7 d is the electrochemical impedance spectra (EIS) of TCN and 3%-FePc / TCN. The principle is that the arc radius is generally positively correlated with the electron transfer barrier, that is, the smaller the arc radius, the smaller the electron transfer barrier. Obviously, the arc radius of 3%-FePc / TCN is smaller than that of TCN. The transient photocurrent and electrochemical impedance data show that after the FePc nanodots are coupled with TCN, the photocurrent intensity increases significantly, and the charge transfer barrier decreases, which effectively improves the degradation efficiency of the photo-Fenton system.
[0074] The above schematically describes the present invention and its implementation methods, which are not restrictive. The drawings show only one implementation method of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and does not deviate from the technical solution of the present invention, and designs a structure and implementation similar to the technical solution based on the above implementation examples without creativity according to the technical essence of the present invention, they should all fall within the protection scope of the present invention.
Claims
1. A tubular triazine TCN / FePc nanodot bifunctional catalyst, characterized in that: The catalyst presents a hollow tubular structure, the length of the hollow tube is about 7.4 μm, the diameter is about 1.6 μm, and there is no obvious pore structure on the triazine tubular carbon nitride, and the thickness is uniform and the surface of the material is rough.
2. The method for preparing a tubular triazine TCN / FePc nanodot bifunctional catalyst according to claim 1, characterized in that: TCN was synthesized using a simple water bath heating and calcination method. The FePc monomer was ground and then mixed with TCN in a certain proportion, and the FePc nanodot / TCN composite photocatalyst was obtained using a calcination method.
3. The method for preparing a tubular triazine TCN / FePc nanodot bifunctional catalyst according to claim 2, characterized in that: Step 1: Preparation of tubular triazine carbon nitride TCN: First, melamine, potassium chloride and lithium chloride are put into an agate grinding body for full grinding for 1 hour, and the ground mixture is placed in a crucible with a cover, and then the ground mixture is placed in a muffle furnace in an air atmosphere for calcination at a heating temperature of 550°C, a heating time of 4 hours, and a heating rate of 5°C / min. Finally, the obtained precursor is centrifugally washed with boiling water and ethanol, and after washing, it is placed in an oven for drying at a heating temperature of 60°C and a heating time of 12 hours to obtain triazine ring structure carbon nitride; Step 2: Preparation of FePc / TCN: The FePc monomer is placed in an agate body and ground for 1 hour, the FePc and TCN monomers are mixed, the precursor is placed in an uncovered porcelain boat and calcined in a tubular furnace in an argon atmosphere, at a heating temperature of 400°C, a heating time of 120 min, and a heating rate of 5°C / min. After calcination, FePc / TCN nano-semiconductor materials can be obtained.
4. A method according to claim 3, characterized in that: The mass ratio of melamine, potassium chloride and lithium chloride is 600 mg:3.3 g:2.7 g.
5. A method according to claim 3, characterized in that: The preparation steps of FePc / TCN, wherein the amount of FePc used is 0.005g or 0.01g or 0.03g or 0.05g, and the amount of TCN used is 1g.
6. Application of a tubular triazine TCN / FePc nanodot bifunctional catalyst, characterized in that: The catalyst is used for antibiotic contaminant removal, especially for tetracycline removal.
7. The use of a tubular triazine TCN / FePc nanodot bifunctional catalyst according to claim 6, characterized in that: A photochemical reactor was used to conduct a photocatalytic degradation experiment on TC under the irradiation of a 300W xenon lamp with a wavelength of λ>420nm to determine the degradation of the sample. First, 3mg~50mg of catalyst was added to 50mL of 20mg / L TC solution, and the reaction was carried out in the dark for 30min to reach adsorption-desorption equilibrium. During this period, 4mL of the suspension was taken out every 10min and centrifuged to obtain the supernatant. 10μL H2O2 was added at the beginning of the photoreaction, and 4mL of the suspension was centrifuged every 20min. The supernatant of the photoreaction process was obtained by centrifugation. Finally, the concentration of TC in each supernatant was determined by a UV-visible spectrophotometer. The formula of photocatalytic degradation rate is: D = (C0-C t ) / C0×100%, Where: C0 is the initial concentration of TC, in mg·L -1 . C t is the concentration of TC after time t, in mg·L -1 .
8. The use of a tubular triazine TCN / FePc nanodot bifunctional catalyst according to claim 7, characterized in that: For every 50 mL of 20 mg / L tetracycline solution, the amount of the catalyst is 3 mg, 5 mg, 10 mg, 20 mg or 50 mg.